Anti-blue-light screen protection film and preparation method thereof

By using a blue light barrier coating solution composed of microcrystalline cellulose, hyaluronic acid and folic acid, an anti-blue light screen protector is formed, which solves the safety hazards and color deviation problems of organic dyes in the prior art, and achieves efficient and environmentally friendly anti-blue light and anti-ultraviolet effects.

CN119708585APending Publication Date: 2025-03-28TAIHU JINZHANG TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411893668.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The existing anti-blue light screen protectors use organic dyes that have heavy metal safety hazards, environmental pollution and color deviation problems, making it difficult to meet the needs of environmental protection and excellent performance.

Method used

A blue light barrier coating liquid composed of microcrystalline cellulose, hyaluronic acid and folic acid is used to form a blue light-proof screen protector through heating and curing, combining a scratch-resistant layer, a substrate layer and a release film layer to improve the blue light and ultraviolet resistance.

Benefits of technology

It achieves efficient blue light and ultraviolet anti-light effects, has good light transmittance, safe and environmentally friendly materials, and is suitable for large-scale industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119708585A_ABST
    Figure CN119708585A_ABST
Patent Text Reader

Abstract

The invention discloses an anti-blue-ray screen protection film and a preparation method thereof, and belongs to the technical field of screen protection film preparation. The anti-blue-light screen protection film comprises a scratch-resistant layer, a base material layer, a blue-light blocking layer and a release film layer, one surface of the base material layer is coated with the scratch-resistant coating, the other surface of the base material layer is coated with the blue light blocking layer, and the other surface of the blue light blocking layer is coated with the release film layer; the blue light blocking layer coating liquid comprises microcrystalline cellulose, hyaluronic acid and folic acid. Ethylenediamine serves as a curing agent to connect the microcrystalline cellulose and the hyaluronic acid, so that the dispersibility and the stability of the microcrystalline cellulose and the hyaluronic acid are further improved, and the ethylenediamine has an effect of absorbing and blocking blue light; amino groups of folic acid are combined with carboxyl groups on hyaluronic acid, so that the ultraviolet-proof performance is improved, and meanwhile, the hardness of the blue light blocking layer is also enhanced by annular groups on folic acid.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of screen protection film preparation, and in particular relates to a blue light protection screen protection film and a preparation method thereof. Background Art

[0002] Studies have shown that blue light, short-wave radiation in the visible spectrum with a wavelength between 380 and 500 nanometers, can penetrate the lens and reach the retina. Long-term exposure to blue light will produce free radicals in the retina, which will promote apoptosis of retinal pigment epithelial cells, resulting in a lack of necessary nutrients for photosensitive cells, which may eventually cause vision damage. It is worth noting that as the wavelength of light waves shortens, the degree of damage to the eyes increases dramatically. Blue light has been proven to be the most potentially harmful part of visible light. Therefore, avoiding exposure to blue light below 480 nanometers is essential to protecting vision.

[0003] Modern flat panel displays, TFT film screens, LEDs, fluorescent lamps, liquid crystal displays, etc. all have backlight sources, and the light sources excited by powerful electron flows all have abnormally high blue light. Therefore, the development of anti-blue light screen protective films for screens on smartphones, LCD TVs and tablets can meet the urgent needs of people who use mobile phones, TVs and computers for a long time. The patent application with publication number CN103935097A discloses an anti-blue light hardening film. The method adopted by the patent is to add a metal complex dye blue light absorber to the anti-blue light layer to achieve the purpose of anti-blue light. However, there are great disadvantages in the preparation of anti-blue light films using organic dyes. For example, the heavy metals in the blue light absorber in the organic dye have safety hazards and can cause environmental pollution. The anti-blue light layer is attached to the outside of the display screen and is in contact with the human body, which is easy to cause personal harm; in addition, after absorbing blue light, the blue light absorber in the organic dye will cause the anti-blue light film to have a serious color deviation, affecting normal use.

[0004] Therefore, developing an anti-blue light protective film with an environmentally friendly and simple preparation process and excellent performance has become an urgent issue to be solved, which is of great significance for protecting people's eyes when using electronic products in daily life. Summary of the invention

[0005] The object of the present invention is to provide a blue light protection screen protective film and a preparation method thereof, so as to improve the blue light protection performance of the screen protective film.

[0006] The purpose of the present invention can be achieved through the following technical solutions:

[0007] A blue light protection screen protective film, comprising a scratch-resistant layer, a substrate layer, a blue light blocking layer and a release film layer;

[0008] The scratch-resistant coating is coated on one side of the substrate layer, the blue light blocking layer is coated on the other side of the substrate layer, and the release film layer is attached to the other side of the blue light blocking layer;

[0009] The blue light blocking layer coating liquid comprises microcrystalline cellulose, hyaluronic acid and folic acid.

[0010] Furthermore, the blue light blocking layer coating liquid is prepared by the following steps:

[0011] Mixing microcrystalline cellulose, hyaluronic acid, ethylenediamine and deionized water, heating for reaction; filtering after cooling, and freeze-drying to obtain hyaluronic acid / microcrystalline cellulose;

[0012] The hyaluronic acid / microcrystalline cellulose is dispersed in PBS buffer to obtain a dispersion; 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride (EDC), N-hydroxysuccinimide (NHS) and folic acid solution are added to the dispersion, and stirred to obtain a blue light blocking layer coating liquid.

[0013] Furthermore, the dosage ratio of the microcrystalline cellulose, hyaluronic acid, ethylenediamine and deionized water is 0.2-0.5 g: 0.1-0.3 g: 0.5-1 mL: 70-80 mL.

[0014] Furthermore, the heating reaction is carried out at 180-200° C. for 5-6 hours.

[0015] Furthermore, the pore size of the filtering membrane is 0.1-0.22 μm.

[0016] Furthermore, the folic acid solution is a solution in which folic acid with a mass fraction of 5% to 10% is dispersed in a dimethyl sulfoxide solution.

[0017] Furthermore, the dosage ratio of the hyaluronic acid / microcrystalline cellulose, PBS buffer, 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, N-hydroxysuccinimide and folic acid solution is 2-3 g: 30-40 mL: 30-45 mg: 10-25 mg: 10-20 mL.

[0018] Furthermore, the stirring time is 22-24h.

[0019] Furthermore, the thickness of the scratch-resistant layer is 5-10 μm; the thickness of the substrate layer is 50-250 μm; the thickness of the blue light blocking layer is 5-15 μm; and the thickness of the release film is 25-75 μm.

[0020] Furthermore, the scratch-resistant layer is formed by curing a scratch-resistant layer coating liquid through ultraviolet light irradiation; the scratch-resistant layer coating liquid is a well-known commercially available product, such as hardening coating liquids of models such as UV-8385, UV-8300 and UV-8380 provided by Xiamen Zhuoyao Technology Co., Ltd.

[0021] Furthermore, the substrate layer is a high-transmittance polyester film; the high-transmittance polyester film is a well-known commercial product, such as the high-transmittance optical-grade polyester film model CH995Y produced by Nan Ya Plastics Industry Co., Ltd.

[0022] Furthermore, the release film layer is a light release film; the light release film is a well-known commercially available product, such as the optical-grade fluorine release film model L31A-L produced by Shenzhen Degussaino Industrial Equipment Co., Ltd.

[0023] A method for preparing a blue light protection screen protective film comprises the following steps:

[0024] S1, coating a scratch-resistant layer coating liquid on one side of the substrate layer, and obtaining a scratch-resistant layer after ultraviolet curing;

[0025] S2, coating a blue light blocking layer coating liquid on the other side of the substrate layer, and heating and curing the coating liquid to obtain a blue light blocking layer;

[0026] S3, covering the other side of the blue light blocking layer with a release film layer to prepare a blue light blocking screen protective film.

[0027] Beneficial effects of the present invention:

[0028] (1) The present invention provides an anti-blue light screen protective film, which comprises, from the outside to the inside, a scratch-resistant layer, a substrate layer, a blue light blocking layer and a release film layer; the protective film provided by the present invention has excellent anti-blue light and anti-ultraviolet effects and good light transmittance; the raw materials used are simple and safe, the preparation method is simple, and is suitable for large-scale industrial production.

[0029] (2) The blue light blocking layer coating liquid provided by the present invention uses microcrystalline cellulose and hyaluronic acid, both of which contain rich hydrogen bonds, which make them have good compatibility. In addition, ethylenediamine acts as a curing agent to connect microcrystalline cellulose and hyaluronic acid, further improving the dispersibility and stability of microcrystalline cellulose and hyaluronic acid, and has an absorption and blocking effect on blue light. The folic acid used in the present invention has an amino group combined with the carboxyl group on the hyaluronic acid, which improves the UV protection performance. At the same time, the cyclic group on the folic acid also enhances the hardness of the blue light blocking layer. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 The present invention is a schematic structural diagram of a blue light protection screen protective film prepared by the present invention. DETAILED DESCRIPTION

[0031] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0032] Example 1

[0033] This embodiment provides a blue light protection screen protective film, which is prepared by the following steps:

[0034] S1. Mix 0.3 g microcrystalline cellulose, 0.2 g hyaluronic acid, 0.8 mL ethylenediamine and 70 mL deionized water, and react at 200° C. for 5 h; cool to room temperature, filter with a 0.22 μm filter membrane, and freeze-dry to obtain hyaluronic acid / microcrystalline cellulose;

[0035] Dispersing 2.5 g of hyaluronic acid / microcrystalline cellulose in 30 mL of PBS buffer to obtain a dispersion; adding 40 mg of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride (EDC), 20 mg of N-hydroxysuccinimide (NHS) and 15 mL of a 10% by mass folic acid / dimethyl sulfoxide solution to the dispersion, stirring for 24 hours, to obtain a blue light blocking layer coating solution;

[0036] S2, coating a scratch-resistant layer coating liquid UV-8385 on one side of a high-transmittance polyester film with a thickness of 150 μm, and obtaining a scratch-resistant layer of 10 μm after ultraviolet curing;

[0037] S3, coating the blue light blocking layer coating liquid on the other side of the high-transmittance polyester film, and obtaining a 10 μm blue light blocking layer after heating and curing;

[0038] S4. A 50 μm light release film layer (L31A-L optical grade fluorine release film) is applied to the other side of the blue light blocking layer to prepare a blue light blocking screen protective film.

[0039] The structure of the anti-blue light screen protector is as follows Figure 1 shown.

[0040] Example 2

[0041] Compared with Example 1, this example is different in that the ratio of microcrystalline cellulose, hyaluronic acid and ethylenediamine is changed. The specific implementation steps of S1 are:

[0042] S1. Mix 0.5 g microcrystalline cellulose, 0.1 g hyaluronic acid, 1 mL ethylenediamine and 70 mL deionized water, and react at 200° C. for 5 h; cool to room temperature, filter with a 0.22 μm filter membrane, and freeze-dry to obtain hyaluronic acid / microcrystalline cellulose;

[0043] Dispersing 2.5 g of hyaluronic acid / microcrystalline cellulose in 30 mL of PBS buffer to obtain a dispersion; adding 40 mg of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride (EDC), 20 mg of N-hydroxysuccinimide (NHS) and 15 mL of a 10% by mass folic acid / dimethyl sulfoxide solution to the dispersion, stirring for 24 hours, to obtain a blue light blocking layer coating solution;

[0044] The remaining raw materials and preparation process remain the same as in Example 1.

[0045] Example 3

[0046] Compared with Example 1, this example is different in that the ratio of microcrystalline cellulose, hyaluronic acid and ethylenediamine is changed. The specific implementation steps of S1 are:

[0047] S1. Mix 0.2 g microcrystalline cellulose, 0.3 g hyaluronic acid, 0.5 mL ethylenediamine and 70 mL deionized water, and react at 200° C. for 5 h; cool to room temperature, filter with a 0.22 μm filter membrane, and freeze-dry to obtain hyaluronic acid / microcrystalline cellulose;

[0048] Dispersing 2.5 g of hyaluronic acid / microcrystalline cellulose in 30 mL of PBS buffer to obtain a dispersion; adding 40 mg of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride (EDC), 20 mg of N-hydroxysuccinimide (NHS) and 15 mL of a 10% by mass folic acid / dimethyl sulfoxide solution to the dispersion, stirring for 24 hours, to obtain a blue light blocking layer coating solution;

[0049] The remaining raw materials and preparation process remain the same as in Example 1.

[0050] Example 4

[0051] Compared with Example 1, this example is different in that the ratio of hyaluronic acid / microcrystalline cellulose, EDC, NHS and folic acid solution is changed. The specific implementation steps of S1 are:

[0052] S1. Mix 0.3 g microcrystalline cellulose, 0.2 g hyaluronic acid, 0.8 mL ethylenediamine and 70 mL deionized water, and react at 200° C. for 5 h; cool to room temperature, filter with a 0.22 μm filter membrane, and freeze-dry to obtain hyaluronic acid / microcrystalline cellulose;

[0053] 3 g of hyaluronic acid / microcrystalline cellulose was dispersed in 30 mL of PBS buffer to obtain a dispersion; 30 mg of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride (EDC), 15 mg of N-hydroxysuccinimide (NHS) and 10 mL of a 10% by mass folic acid / dimethyl sulfoxide solution were added to the dispersion and stirred for 24 hours to obtain a blue light blocking layer coating solution;

[0054] The remaining raw materials and preparation process remain the same as in Example 1.

[0055] Example 5

[0056] Compared with Example 1, this example is different in that the ratio of hyaluronic acid / microcrystalline cellulose, EDC, NHS and folic acid solution is changed. The specific implementation steps of S1 are:

[0057] S1. Mix 0.3 g microcrystalline cellulose, 0.2 g hyaluronic acid, 0.8 mL ethylenediamine and 70 mL deionized water, and react at 200° C. for 5 h; cool to room temperature, filter with a 0.22 μm filter membrane, and freeze-dry to obtain hyaluronic acid / microcrystalline cellulose;

[0058] 2 g of hyaluronic acid / microcrystalline cellulose was dispersed in 30 mL of PBS buffer to obtain a dispersion; 45 mg of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride (EDC), 25 mg of N-hydroxysuccinimide (NHS) and 20 mL of a 10% by mass folic acid / dimethyl sulfoxide solution were added to the dispersion and stirred for 24 hours to obtain a blue light blocking layer coating solution;

[0059] The remaining raw materials and preparation process remain the same as in Example 1.

[0060] Example 6

[0061] Compared with Example 1, this embodiment is different in that the thickness ratios of the scratch-resistant layer, the substrate layer, the blue light blocking layer and the release film are different. The specific implementation steps of S2-S4 are:

[0062] S2, coating a scratch-resistant layer coating liquid UV-8385 on one side of a high-transmittance polyester film with a thickness of 200 μm, and obtaining a 5 μm scratch-resistant layer after ultraviolet curing;

[0063] S3, coating the blue light blocking layer coating liquid on the other side of the high-transmittance polyester film, and after heating and curing, obtaining a 15 μm blue light blocking layer;

[0064] S4. A 75 μm light release film layer (L31A-L optical grade fluorine release film) is applied to the other side of the blue light blocking layer to prepare a blue light blocking screen protective film.

[0065] The remaining raw materials and preparation process remain the same as in Example 1.

[0066] Example 7

[0067] Compared with Example 1, this embodiment is different in that the thickness ratios of the scratch-resistant layer, the substrate layer, the blue light blocking layer and the release film are different. The specific implementation steps of S2-S4 are:

[0068] S2, coating a scratch-resistant layer coating liquid UV-8385 on one side of a high-transmittance polyester film with a thickness of 100 μm, and obtaining a scratch-resistant layer of 10 μm after ultraviolet curing;

[0069] S3, coating the blue light blocking layer coating liquid on the other side of the high-transmittance polyester film, and after heating and curing, obtaining a 5 μm blue light blocking layer;

[0070] S4. A 25 μm light release film layer (L31A-L optical grade fluorine release film) is applied to the other side of the blue light blocking layer to prepare a blue light blocking screen protective film.

[0071] The remaining raw materials and preparation process remain the same as in Example 1.

[0072] Comparative Example 1

[0073] Compared with Example 1, this comparative example differs in that hyaluronic acid is not added, and the specific implementation steps of S1 are:

[0074] S1. Mix 0.3 g of microcrystalline cellulose, 0.8 mL of ethylenediamine and 70 mL of deionized water, and react at 200° C. for 5 h; cool to room temperature, filter with a 0.22 μm filter membrane, and lyophilize to obtain a mixture;

[0075] Disperse 2.5 g of the mixture in 30 mL of PBS buffer to obtain a dispersion; add 40 mg of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride (EDC), 20 mg of N-hydroxysuccinimide (NHS) and 15 mL of a 10% by mass folic acid / dimethyl sulfoxide solution to the dispersion, and stir for 24 hours to obtain a blue light blocking layer coating solution;

[0076] The remaining raw materials and preparation process remain the same as in Example 1.

[0077] Comparative Example 2

[0078] Compared with Example 1, this comparative example differs in that folic acid is not added, and the specific implementation steps of S1 are:

[0079] S1. Mix 0.3 g microcrystalline cellulose, 0.2 g hyaluronic acid, 0.8 mL ethylenediamine and 70 mL deionized water, and react at 200° C. for 5 h; cool to room temperature, filter with a 0.22 μm filter membrane, and freeze-dry to obtain hyaluronic acid / microcrystalline cellulose;

[0080] 2.5 g of hyaluronic acid / microcrystalline cellulose was dispersed in 30 mL of PBS buffer to obtain a dispersion; 40 mg of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride (EDC) and 20 mg of N-hydroxysuccinimide (NHS) were added to the dispersion and stirred for 24 hours to obtain a blue light blocking layer coating solution;

[0081] The remaining raw materials and preparation process remain the same as in Example 1.

[0082] Comparative Example 3

[0083] Compared with Example 1, the difference between this comparative example is that hyaluronic acid and folic acid are not added at the same time, and the specific implementation steps of S1 are:

[0084] S1. Mix 0.3 g of microcrystalline cellulose, 0.8 mL of ethylenediamine and 70 mL of deionized water, and react at 200° C. for 5 h; cool to room temperature, filter with a 0.22 μm filter membrane, and lyophilize to obtain a mixture;

[0085] 2.5 g of the mixture was dispersed in 30 mL of PBS buffer to obtain a dispersion; 40 mg of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride (EDC) and 20 mg of N-hydroxysuccinimide (NHS) were added to the dispersion and stirred for 24 hours to obtain a blue light blocking layer coating solution;

[0086] The remaining raw materials and preparation process remain the same as in Example 1.

[0087] Comparative Example 4

[0088] Compared with Example 1, this comparative example differs in that no microcrystalline cellulose is added, and the specific implementation steps of S1 are as follows:

[0089] S1. Mix 0.2 g hyaluronic acid, 0.8 mL ethylenediamine and 70 mL deionized water, and react at 200° C. for 5 h. After cooling to room temperature, filter with a 0.22 μm filter membrane, and lyophilize to obtain a mixture.

[0090] Disperse 2.5 g of the mixture in 30 mL of PBS buffer to obtain a dispersion; add 40 mg of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride (EDC), 20 mg of N-hydroxysuccinimide (NHS) and 15 mL of a 10% by mass folic acid / dimethyl sulfoxide solution to the dispersion, and stir for 24 hours to obtain a blue light blocking layer coating solution;

[0091] The remaining raw materials and preparation process remain the same as in Example 1.

[0092] Comparative Example 5

[0093] Compared with Example 1, this comparative example differs in that no blue light blocking layer is added, and the specific implementation steps are as follows:

[0094] S1. Mix 0.3 g microcrystalline cellulose, 0.2 g hyaluronic acid, 0.8 mL ethylenediamine and 70 mL deionized water, and react at 200° C. for 5 h; cool to room temperature, filter with a 0.22 μm filter membrane, and freeze-dry to obtain hyaluronic acid / microcrystalline cellulose;

[0095] Dispersing 2.5 g of hyaluronic acid / microcrystalline cellulose in 30 mL of PBS buffer to obtain a dispersion; adding 40 mg of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride (EDC), 20 mg of N-hydroxysuccinimide (NHS) and 15 mL of a 10% by mass folic acid / dimethyl sulfoxide solution to the dispersion, stirring for 24 hours, to obtain a blue light blocking layer coating solution;

[0096] S2, coating a scratch-resistant layer coating liquid UV-8385 on one side of a high-transmittance polyester film with a thickness of 150 μm, and obtaining a scratch-resistant layer of 10 μm after ultraviolet curing;

[0097] S3. A 50 μm light release film layer (L31A-L optical grade fluorine release film) is applied to the other side of the high-transmittance polyester film to prepare a screen protection film.

[0098] The remaining raw materials and preparation process remain the same as in Example 1.

[0099] Performance Test:

[0100] 1. Blue light blocking rate: The blue light blocking rate of the anti-blue light screen protective films obtained in each embodiment and comparative example of the present application is tested using a spectrophotometer;

[0101] 2. Light transmittance: Use a light transmittance tester to test the light transmittance of the anti-blue light screen protective films obtained in various embodiments and comparative examples of the present application;

[0102] 3. Ultraviolet blocking rate: According to GB / T 2680-2021, the ultraviolet blocking rate of the anti-ultraviolet automotive film obtained in each embodiment and comparative example of the present application is tested;

[0103] 4. Hardness: According to GB / T6739-2022, the anti-blue light screen protective films obtained in various embodiments and comparative examples of the present application were subjected to a scratch resistance hardness test;

[0104] The results are shown in Table 1:

[0105] Table 1

[0106]

[0107] From the comparative examples and Table 1, it can be seen that the difference between Examples 2-5 and Example 1 is only the change in the raw material ratio within a reasonable range during the preparation of the blue light blocking layer coating liquid; the difference between Examples 6-7 and Example 1 is the different thickness ratios of the scratch-resistant layer, substrate layer, blue light blocking layer and release film. From the test results, the obtained anti-blue light protective films all have excellent performance.

[0108] Compared with Example 1, after not adding hyaluronic acid, Comparative Example 1 has a decreased blue light blocking performance on the one hand, and on the other hand, the amino group on the folic acid in the system cannot combine with microcrystalline cellulose, which reduces the dispersibility of the entire system; Compared with Example 1, after not adding folic acid, the ultraviolet blocking rate of the protective film in Comparative Example 2 is greatly reduced, and the hardness is also reduced; and compared with Comparative Examples 1-2 and Example 1, after not adding hyaluronic acid and folic acid at the same time, Comparative Example 3 has a decreased dispersibility of the material, which affects the blue light blocking effect of the material, and the ultraviolet protection and hardness are reduced. This is because the amino group on folic acid combines with the carboxyl group on hyaluronic acid, which improves the ultraviolet light protection performance, and the cyclic group on folic acid also enhances the hardness of the blue light blocking layer; Compared with Example 1 and Comparative Examples 1-3, the blue light blocking rate of Comparative Example 4 drops sharply, which shows that the microcrystalline cellulose, hyaluronic acid and ethylenediamine system has a good blue light protection effect; Comparative Example 5 is equivalent to the blank control.

[0109] In summary, the present invention provides an anti-blue light screen protective film and a preparation method thereof. The preparation process is simple, and the prepared anti-blue light screen protective film has good anti-blue light and anti-ultraviolet effects while taking into account light transmittance, and is suitable for large-scale industrial production.

[0110] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0111] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A blue light protection screen protective film, characterized in that: The anti-blue light screen protective film comprises a scratch-resistant layer, a substrate layer, a blue light blocking layer and a release film layer; The scratch-resistant coating is coated on one side of the substrate layer, the blue light blocking layer is coated on the other side of the substrate layer, and the release film layer is attached to the other side of the blue light blocking layer; The blue light blocking layer coating liquid comprises microcrystalline cellulose, hyaluronic acid and folic acid.

2. The anti-blue light screen protective film according to claim 1, characterized in that: The blue light blocking layer coating liquid is prepared by the following steps: Mixing microcrystalline cellulose, hyaluronic acid, ethylenediamine and deionized water, heating for reaction; filtering after cooling, and freeze-drying to obtain hyaluronic acid / microcrystalline cellulose; The hyaluronic acid / microcrystalline cellulose is dispersed in PBS buffer to obtain a dispersion; 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, N-hydroxysuccinimide and folic acid solution are added to the dispersion, and stirred to obtain a blue light blocking layer coating liquid.

3. The anti-blue light screen protective film according to claim 2, characterized in that: The dosage ratio of the microcrystalline cellulose, hyaluronic acid, ethylenediamine and deionized water is 0.2-0.5 g: 0.1-0.3 g: 0.5-1 mL: 70-80 mL.

4. The anti-blue light screen protective film according to claim 2, characterized in that: The heating reaction is carried out at 180-200° C. for 5-6 hours.

5. The anti-blue light screen protective film according to claim 2, characterized in that: The pore size of the filtering membrane is 0.1-0.22 μm.

6. The anti-blue light screen protective film according to claim 2, characterized in that: The folic acid solution is a solution in which folic acid with a mass fraction of 5% to 10% is dispersed in a dimethyl sulfoxide solution.

7. The anti-blue light screen protective film according to claim 2, characterized in that: The dosage ratio of the hyaluronic acid / microcrystalline cellulose, PBS buffer, 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, N-hydroxysuccinimide and folic acid solution is 2-3 g: 30-40 mL: 30-45 mg: 10-25 mg: 10-20 mL.

8. The anti-blue light screen protective film according to claim 2, characterized in that: The stirring time is 22-24h.

9. The anti-blue light screen protective film according to claim 1, characterized in that: The thickness of the scratch-resistant layer is 5-10 μm; the thickness of the substrate layer is 50-250 μm; the thickness of the blue light blocking layer is 5-15 μm; and the thickness of the release film is 25-75 μm.

10. A method for preparing the anti-blue light screen protective film according to any one of claims 1 to 9, characterized in that: The following steps are involved: S1, coating a scratch-resistant layer coating liquid on one side of the substrate layer, and obtaining a scratch-resistant layer after ultraviolet curing; S2, coating a blue light blocking layer coating liquid on the other side of the substrate layer, and heating and curing the coating liquid to obtain a blue light blocking layer; S3, covering the other side of the blue light blocking layer with a release film layer to prepare a blue light blocking screen protective film.

Citation Information

Patent Citations

  • Blue-proof hardening film

    CN103935097A